Archaeal transcription and replication: new insights into transcription-coupled DNA repair and origin-independent DNA replication - Gehring, Alexandra Marie, author; Santangelo, Thomas, advisor; Argueso, J. Lucas, committee member; Nyborg, Jennifer K., committee member; Peersen, Olve B., committee member (Colorado State University. Libraries, 2017)
The three Domains of extant life use similar mechanisms for information processing systems. Although many aspects of replication, transcription and translation are universally conserved, the evolutionary history of the enzymes involved is not always clear and domain-specific differences are known. The transcription apparatus, especially the multi-subunit RNA polymerase (RNAP), has a clear evolutionary conservation across all Domains. Elucidating the mechanisms of the transcription apparatus in Archaea will help further understanding of underlying transcription mechanisms and regulation of those mechanisms, not only in Archaea but also in Bacteria and Eukarya. Conversely, the DNA replication machinery, most notably the replicative DNA polymerases, are distinct for each Domain. Any demonstration of the activities of the replication proteins, and especially discovery of unique pathways and mechanisms underlying replication helps to improve the understanding of the larger evolutionary questions surrounding DNA replication. The compact nature of archaeal genomes necessitates timely termination of transcription to prevent continued transcription of neighboring genes while ensuring complete transcription of the gene of interest. Transcription elongation is processive, and the transcription elongation complex is exceptionally stable. The disruption of this transcription elongation process, transcription termination, is an essential step in the transcription cycle. The presence of DNA lesions causes early termination of transcription in Bacteria and Eukarya. The results of this dissertation demonstrate this is also true in Archaea. Archaeal RNAP arrests transcription at DNA lesions and likely initiates transcription-coupled DNA repair (TCR) as will be soon demonstrated using in vivo techniques developed during this dissertation work. DNA replication is a highly regulated cellular process, particularly initiation of DNA replication. The long-standing replicon hypothesis states a trans-acting replication initiation protein must recognize a cis-acting DNA element, the origin of replication. For the 50 years after the replicon hypothesis was first posited, the replication hypothesis was supported in phages, Bacteria, Archaea, and Eukarya. The work presented in this dissertation describes the non-essentiality of Cdc6 and the origin of replication, and further demonstrates that origin-independent DNA replication is the mechanism by which Thermococcus kodakarensis replicates its genome. The results of this study and others in the field brings forward questions about the evolutionary history of DNA replication in all three Domains of extant life.
Keywords: replication; transcription; Thermococcus kodakarensis; Archaea